2004
DOI: 10.1111/j.1365-2249.2004.02623.x
|View full text |Cite
|
Sign up to set email alerts
|

Allogenic donor splenocytes pretreated with antisense peptide against B7 prolong cardiac allograft survival

Abstract: SUMMARYThe interaction of T cell CD28/CTLA-4 receptors with B7 on antigen-presenting cells (APCs) represents an important co-stimulatory pathway in T cell activation or anergy. Our previous study indicated that recipients immunized with allogenic donor immature dendritic cells (DCs) or resting B cells could induce specific immune tolerance and prolong allograft survival. A possible mechanism for this observation is that the expression of B7 molecules is either at a low level or lacking on these cells. The pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
2

Year Published

2008
2008
2014
2014

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 32 publications
0
10
0
2
Order By: Relevance
“…In order to investigate the application of SAgAs targeting the B7 pathway, we selected three peptides (B7AP, CD80-CAP, sF2), which had been previously reported to bind B7 (Table I). Two peptides used in this study, B7AP and CD80-CAP, have been shown to inhibit inflammatory immune response in several rodent autoimmune models (18)(19)(20)30,37). In contrast, the peptide mimic of CTLA-4 (sF2) was originally selected for this study as a positive control to enhance the immune response by blocking the B7:CTLA-4 regulatory interactions (31).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to investigate the application of SAgAs targeting the B7 pathway, we selected three peptides (B7AP, CD80-CAP, sF2), which had been previously reported to bind B7 (Table I). Two peptides used in this study, B7AP and CD80-CAP, have been shown to inhibit inflammatory immune response in several rodent autoimmune models (18)(19)(20)30,37). In contrast, the peptide mimic of CTLA-4 (sF2) was originally selected for this study as a positive control to enhance the immune response by blocking the B7:CTLA-4 regulatory interactions (31).…”
Section: Discussionmentioning
confidence: 99%
“…Peptides selected for use in this study were previously shown to interact with and modulate the B7 signaling pathway (Table I) (18)(19)(20)30,31). SAgAs targeting the B7 pathway were created by co-grafting to hyaluronic acid polymers (HA) both autoantigen (PLP 139-151 ) and B7-binding peptides (B7AP, CD80-CAP, or sF2) as previously reported (15,24,25).…”
Section: Synthesis and Characterization Of Soluble Antigen Arraysmentioning
confidence: 99%
See 1 more Smart Citation
“…Engagement of B7-1 or B7-2 on APCs with CD28 on T cells provides costimulatory signals that are required for the activation of naïve T cells, and T-cell responses are severely inhibited in Cd28 -knockout (KO) mice [5,6]. The interaction of CTLA-4 with the same ligands acts as a negative regulator of CD28-dependent T-cell activation [7,8], and loss of CTLA-4 leads to severe lymphoproliferation and fatal multiorgan destruction via autoimmunity [9]. In this way, the B7-1/B7-2–CD28/CTLA-4 pathway represents either a costimulatory or coinhibitory pathway in modulating the T-cell response.…”
Section: Characteristics Of the B7 Family Membersmentioning
confidence: 99%
“…Peptides derived from the conserved region of CD28 containing the motif MYPPPY bind to B7 and have suppressed EAE in B10.PL mice [136]. A similar but shorter peptide that showed efficacy in prolonging cardiac allograft rejection [137] was tested in our laboratory, and results indicated significant suppression of PLP 139-151 -induced EAE in SJL/J mice (unpublished data).…”
Section: Peptide Treatments For Msmentioning
confidence: 99%